Living in the face of menacing ‘unreason’ - Martin Amis's "The Second Plane" as a response to ideological fundamentalisms - Bartnik, Ryszard (Adam Mickiewicz University, 2010)
This work touches upon Martin Amis’s diagnosis of the Western world and its cultural foundations which seem to have been threatened, as maintained by the author, by a specific form of “de- Enlightenment” (2008). Amis, a repository of Western intellectual ethos, steps to the fore to defend reason. In view of the world’s unrests, he fosters a thorough investigation of public beliefs, either of a religious or political nature, highlighting how deeply individual freedom has been censored and imperiled by various fundamentalisms. In his highly controversial, often blasphemous, collection of essays and short stories titled The second plane Amis renounces in an uncompromising way religious militancy, intellectual insularity, and political dogmatism. Politically incorrect and willfully offensive, the novelist appears unsparing in his criticism of Islamic integrity and right-wing ‘theological’ intransigence. My intention, thus, is to discuss Amis’s overall standpoint referring both to the short story “The last days of Muhammad Atta” and a number of his articles written between 2002-2007.